Land use for bioenergy: Synergies and trade-offs between sustainable development goals. (June 2022) - Vera, Ivan; Wicke, Birka; Lamers, Patrick; Cowie, Annette; Repo, Anna; Heukels, Bas; Zumpf, Colleen; Styles, David; Parish, Esther; Cherubini, Francesco; Berndes, Göran; Jager, Henriette; et al.
Abstract: Bioenergy aims to reduce greenhouse gas (GHG) emissions and contribute to meeting global climate change mitigation targets. Nevertheless, several sustainability concerns are associated with bioenergy, especially related to the impacts of using land for dedicated energy crop production. Cultivating energy crops can result in synergies or trade-offs between GHG emission reductions and other sustainability effects depending on context-specific conditions. Using the United Nations Sustainable Development Goals (SDGs) framework, the main synergies and trade-offs associated with land use for dedicated energy crop production were identified. Furthermore, the context-specific conditions (i.e., biomass feedstock, previous land use, climate, soil type and agricultural management) which affect those synergies and trade-offs were also identified. The most recent literature was reviewed and a pairwise comparison between GHG emission reduction (SDG 13) and other SDGs was carried out. A total of 427 observations were classified as either synergy (170), trade-off (176), or no effect (81). Most synergies with environmentally-related SDGs, such as water quality and biodiversity conservation, were observed when perennial crops were produced on arable land, pasture or marginal land in the 'cool temperate moist' climate zone and 'high activity clay' soils. Most trade-offs were related to food security and water availability. Previous land use and feedstock type are more impactful in determining synergies and trade-offs than climatic zone and soil type. This study highlights the importance of considering context-specific conditions in evaluating synergies and trade-offs and their relevance for developing appropriate policies and practices to meet worldwide demand for bioenergy in a sustainable manner. Highlights: Synergies and trade-offs between SDGs from land use for bioenergy. Synergies are related to water quality, soil quality and biodiversity conservation. Trade-offs are related to water availability, food security and revenue. Previous land use and feedstock are more relevant than other context conditions.